Estudio de la interconexión en media tensión de los batch switch (switch vista) de la ciudadela Belohorizonte. - Vargas Vergara, Eulogio Alejandro (2019)
The electrical system has the function of distributing electrical energy reliably, continuously and safely. Despite this, there are inconsistencies and variations in the electrical system resulting from transient electrical phenomena, operating conditions or the way the power supply is supplied. Currently, there is an interruption of electric power that harms the users of Belohorizonte at the time of performing a maneuver at the medium voltage (M / T) level in the switch seen. For this reason the objective is to perform a correct survey for the study of the interconnection of the view switches, in medium voltage in the Belohorizonte citadel. For the implementation of the correct route of the underground lines of 15kV. This line will serve to provide electric power from the main view switch, making the tour through the 4 switches seen next. Parallel connection with the five Switch view located within the Belohorizonte citadel and powered by two different feeders connected in parallel, the switches seen through the B and C routes feed the single-phase PadMounted transformers connected to each other, several transformers. The methodology applied to this project is descriptive, and empirical, it details the problem of the wiring phases, this happens because the phases (A, B, C) of the network do not have the appropriate phase sequence or marked with colored ribbons. Likewise, information gathering will be carried out and electrical plans for connections and delineation of the aforementioned lines will be drawn up. In this design, the basic aspects demanded by the CNEL, ep Guayaquil, in the approval of works carried out by electrical design professions, demand calculation, technical memory, as well as norms and qualities that are taken into account at national level, are pointed out. , the design was elaborated according to the methodology, specific criteria and procedures established in the NATSIN.